Three-Dimensional Structure of Drosophila Testis Tip: The Spatial Relation Between Dividing Cells - Lee, Kyung Eun; Han, Sung Sik; Jeon, Hyesung (CAMBRIDGE UNIV PRESS, 2013)
At the apical tip of Drosophila testis, there is a stem cell niche known as the proliferation center, where the stem cells are maintained by hub cell cluster for the regulation of differentiation and proliferation. Germline stem cells go through mitosis four times from one primary spermatogonial cell to the 16-cell stage before the maturation. The cells derived from the same germline stem cell are located within one cyst, an enclosed system by two cyst cells, and they are connected by the intercellular bridges called ring canals. In this study, the three-dimensional (3D) structure of Drosophila testis tip was reconstructed from serial sections. The size of cells at each stage was compared in volume from the 3D structure. The stages of cells in a cyst could be distinguishable exactly by counting the cells linked with intercellular bridges in 3D-reconstructed structure. The cysts containing the same stage cells appeared in the horizontal plane. Both the germline stem cell directly attached to the hub cell and the spermatogonial cells detached from the hub cell were divided at the almost perpendicular direction to the spermatogonial cell layers. The dividing phase in one cyst was delayed gradually through the cytoplasmic region of intercellular bridge.
Keywords: OOCYTE SPECIFICATION; GERM-LINE; FUSOME; COMPONENTS; CYST